Assessment of the quality of determining the coordinates of air objects by cooperative radar systems for air surveillance - Svyd, I.V.; Obod, I.I.; Holovatenko, S.V.; Datsko , S.V. (Radiotekhnika, 2023)
In the presented work, based on the classification of airspace surveillance radar systems in the form: independent non-cooperative radar surveillance, independent cooperative radar surveillance, dependent cooperative radar surveillance; the quality of determining the coordinates of air objects by the systems under study was assessed. The place and role of these information systems in the information support of airspace control and air traffic control systems is shown. From the calculations carried out, we can draw the following conclusion that the sensitivity of measuring the height of an airborne object significantly depends on the geometry of the location of receiving points of a synchronous network of radar surveillance systems. As the distance between receiving points increases, the area covered by curves of equal sensitivity increases. It is substantiated that when using equal weight in the accuracy of range measurement and in measuring the altitude of an airborne object, the accuracy of the synchronization of the time scales of the receiving points is the value achieved by modern means of time synchronization. The use of the given methodology for assessing the quality of measuring the coordinates of air objects in a synchronous network of cooperative radar surveillance systems for airspace allows us to put forward requirements for the synchronism of time scales in a unified synchronous information network of radar surveillance systems when measuring the coordinates of air objects. It is shown that the price for improving the accuracy of determining the coordinates of air objects by a synchronous network of cooperative radar systems is the complication of the system due to an increase in positions, an increase in the number of transceiver paths, the need to synchronize emission processes, receive signals and control viewing modes.